2022
DOI: 10.1038/s41467-022-29742-2
|View full text |Cite
|
Sign up to set email alerts
|

A computational theory of the subjective experience of flow

Abstract: Flow is a subjective state characterized by immersion and engagement in one’s current activity. The benefits of flow for productivity and health are well-documented, but a rigorous description of the flow-generating process remains elusive. Here we develop and empirically test a theory of flow’s computational substrates: the informational theory of flow. Our theory draws on the concept of mutual information, a fundamental quantity in information theory that quantifies the strength of association between two va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…To the extent that 𝐼(𝑀; 𝐸) really does underlie flow, it also serves as an answer to the basic question of how representations of task structure and flow interact, and as a tool that can help people harness flow in their daily lives. It remains to be seen whether the informational theory of flow stands up to empirical scrutiny, though initial tests give reason for optimism (Melnikoff et al, 2022). Regardless, testing the predictions presented in this chapter would yield valuable insights, and, we believe, should be a major item on the agenda for future research.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…To the extent that 𝐼(𝑀; 𝐸) really does underlie flow, it also serves as an answer to the basic question of how representations of task structure and flow interact, and as a tool that can help people harness flow in their daily lives. It remains to be seen whether the informational theory of flow stands up to empirical scrutiny, though initial tests give reason for optimism (Melnikoff et al, 2022). Regardless, testing the predictions presented in this chapter would yield valuable insights, and, we believe, should be a major item on the agenda for future research.…”
Section: Discussionmentioning
confidence: 86%
“…Critically, mutual information is one of many ways of quantifying associative strength. We have shown that it outperforms other metrics as a predictor of flow (Melnikoff et al, 2022), but it may not fare as well as a predictor of other self-regulatory phenomena.…”
Section: Modeling Goal Systemsmentioning
confidence: 83%
See 2 more Smart Citations
“…This view comports with accounts that operationalize effort and information as inherently rewarding, to explain seemingly irrational behavior (Inzlicht, Shenhav, & Olivola, 2018). Furthermore, accounts on flow (Csikszentmihalyi, 1990;Melnikoff, Carlson, & Stillman, 2022;Wilson, Shenhav, Straccia, & Cohen, 2019), boredom (Geana, Wilson, Daw, & Cohen, 2016), curiosity (Schmidhuber, 1991), and fatigue (Agrawal et al, 2021) suggest mechanisms for investing cognitive resources not only to accommodate current bounds, but to optimally change those bounds. In line with normative theories of learning (Dubey & Griffiths, 2020;Kidd & Hayden, 2015), human infants and macaques will allocate attention to stimuli that are intermediately surprising (Cubit, Canale, Handsman, Kidd, & Bennetto, 2021;Wu et al, 2021), and adults will self-organize their curricula to maximize learning and reward (e.g., Ten, Kaushik, Oudeyer, & Gottlieb, 2021).…”
Section: Cognitive Agents May Consider the Modification Of Cognitive ...mentioning
confidence: 89%